Pattern of pericardial diseases in HIV-positive patients at University College Hospital, Ibadan, Nigeria - Umar Abubakar; P O Adeoye; O A Adebo; V O Adegboye; E B Kesieme; E K Okonta (AOSIS, 2011)
Rationale. Pericarditis has been reported as the most common cardiac complication of HIV disease, followed by pericardial effusion. Methods. A retrospective review was conducted of all 68 patients treated for pericardial diseases between August 2003 and July 2008 at University College Hospital, Ibadan, Nigeria. HIV-positive patients (N=42) were compared with those who were HIV negative (N=26). Results. More male than female patients presented with pericardial disease, and the HIV-positive patients were younger than those who were HIV negative. Pericardial effusion was the commonest mode of presentation, accounting for 20 HIV-positive patients (47.7%) and 13 HIV-negative patients (50%). Pericardiostomy was the commonest surgical intervention performed in HIV-positive patients (N=15), while the majority of HIV-negative patients had pericardiocentesis. Conclusion. Pericardial effusion was the commonest cardiac presentation in HIV-positive patients in our setting. We recommend that patients with pericardial effusion be investigated for HIV infection.